Impact of participant and interventionist race concordance on weight loss outcomes12. (25th May 2013) - Batch, Bryan C.; Ard, Jamy D.; Vollmer, William M.; Funk, Kristine; Appel, Lawrence J.; Stevens, Victor J.; Samuel‐Hodge, Carmen; Loria, Catherine M.; Hollis, Jack F.; Svetkey, Laura P.
Abstract: Objective: We have previously shown that racial composition of behavioral intervention groups does not affect achieved weight loss. However, it is unclear if the race of the interventionist affects intervention outcomes. The objective of this analysis is to estimate the impact of race concordance between participant and interventionist on weight change in the initial weight loss phase (phase I) of the Weight Loss Maintenance trial (WLM). Design and Methods: A total of 1, 685 overweight or obese adults (BMI 25‐45 kg/m 2 ) who were taking medication for hypertension and/or dyslipidemia participated in phase I of the WLM trial. All participants received a 6‐month intensive behavioral intervention in groups of 15‐20 facilitated by a trained interventionist. The main outcome is change in weight at 6 months. Results: Participants were on average 55 years of age, 67% female and 44% African American (AA). Three of seventeen interventionists were AA, 14 were non‐AA. Seventy‐three percent of participants shared race concordance with the interventionist. There was a small but statistically significant difference in weight change of participants who were the same race as the interventionist (−5.84 kg, s.e. 0.17) as compared with those who were not race concordant (−5.04 kg, s.e. 0.33), a difference of 0.8 kg, ( P = 0.04). The impact of concordance on weight change differed by race (i.e., interaction of race and concordance was significant, P = 0.02). Conclusions: In a post hoc analysis of a group‐based behavioral intervention, race concordance for non‐AA participants was associated with slightly greater weight loss. Race concordance was not associated with weight loss for AA participants.